Academic Administration Based on the Four Iddhipāda Principles of School Administrators under the Office of Nong Bua Lamphu Primary Educational Service Area 1 - Amatathongchai, Chob; Kangpeng, Samrit; Chantarasombat, Chalard (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to study academic administration based on the Four Iddhipāda Principles practiced by school administrators under the Office of Nong Bua Lamphu Primary Educational Service Area 1 and to propose guidelines for academic administration grounded in these principles. The research employed a mixed methods approach. The quantitative part involved a survey with 322 participants, while the qualitative part included in-depth interviews with 12 key informants. Quantitative data were analyzed using basic statistics, and qualitative data were analyzed through content analysis. The research results were as follows: 1. Academic administration based on the Four Iddhipāda Principles among school administrators under the Office of Nong Bua Lamphu Primary Educational Service Area 1 consisted of various dimensions. The highest level of implementation was found in administration based on Viriya (effort), followed by Citta (concentration), Vīmaṁsā (investigation), and Chanda (aspiration), respectively. 2. The proposed guidelines for academic administration based on the Four Iddhipāda Principles emphasize love and faith in one’s role, a clear commitment to goals, and strengthening teachers’ skills in using technology and creative teaching methods. With the aim is to improve curricula so that they are appropriately aligned with the context of each school and its surrounding community.